Transitional justice and civil war: exploring new pathways, challenging old guideposts - Reiter, A; Olsen, T; Payne, L (Western University, 2013)
Transitional justice has shifted from its primary use in addressing past atrocities of authoritarian regimes to those acts of violence committed during civil wars. Yet the use of transitional justice mechanisms in this new context is not well understood. Drawing from the existing transitional justice literature, this article generates a set of testable hypotheses to explore which factors influence the use of particular mechanisms during and after conflict. It then tests those hypotheses in 151 cases of civil war by using a cross-national data base of all countries in the world and their adoption of transitional justice